Graphs & digraphs - Chartrand, Gary 1936-; Lesniak, Linda 1948- (Chapman & Hall, 2005)
"With a growing range of applications in fields from computer science to chemistry and communications networks, graph theory has enjoyed a rapid increase of interest and widespread recognition as an important area of mathematics. Through more than 20 years of publication, Graphs & Digraphs has remained a popular point of entry to the field, and through its various editions, has evolved with the field from a purely mathematical treatment to one that also addresses the mathematical needs of computer scientists. Carefully updated, streamlined, and enhanced with new features, Graphs & Digraphs, Fourth Edition reflects many of the developments in graph theory that have emerged in recent years. The authors have added discussions on topics of increasing interest, deleted outdated material, and judiciously augmented the Exercises sections to cover a range of problems that reach beyond the construction of proofs." -- Book cover.
Keywords: Grafentheorie; Graphes orientés; Graphes, Théorie des; Directed graphs; Graph theory; Gerichteter Graph; Graphentheorie